Antioksidan Vitamin dan Kerusakan Otot pada Aktivitas Fisik Studi Eksperimen pada Mahasiswa JPOK-FKIP UNS Surakarta - Kiyatno Kiyatno (MEDIA MEDIKA INDONESIANA, 2009)
Vitamin antioxidants administration toward muscle damage on exercise. An experimental study in students of FKIP–JPOK Sebelas Maret UniversityBackground: Exercise has dual effects, which not only enhance health status and performance but also results in muscular damage. The aim of this study is to determine when the administration of vitamin antioxidants is more effective in reducing the muscular damage.Methods: An experimental quantitative study with a 2x2 factorial research design was used in this study. Forty of total students in third semester of JPOK-FKIP Sebelas Maret University were randomly selected to become the experimental subjects and divided equally into four groups. First and second groups performed exercise with strenuous sub maximal intensity (SSI, running 2x800 m) and took the vitamin antioxidants (30 mg vitamin A, 200 mg vitamin C, 50 mg vitamin E, 15 mg Zn and 25 mcg Se) before runningfor first group and after running for second group respectively. Prior to perform prolonged sub maximal intensity (PSI, running 1500 m) third group took the same antioxidants while fourth group took the antioxidant after doing PSI. 48 hours later, MDA plasma levels were determined by using TBARS in order to measure the muscular damage. T-test was use for analyzing all collected data.Results: There is different effect on muscle damage when vitamin antioxidants were taken before and after exercise (obs.T 3.70> tb.T 1.68), which vitamin antioxidants were taken after exercise has a better muscle damage (MDA 200.60><222.38).Conclusions: The administration of vitamin antioxidants after exercise has a better muscle damage.Keywords: Exercise, vitamin antioxidants, muscle damageABSTRAK Latar belakang: Aktivitas fisik selain membuat tubuh menjadi lebih sehat dan lebih bugar, juga dapat menimbulkan kerusakan otot. Tujuan penelitian untuk mengetahui waktu pemberian antioksidan vitamin yang paling efektif untuk mengurangi kerusakan otot.Metode: Jenis penelitian adalah kuantitatif–eksperimental menggunakan rancangan penelitian faktorial 2x2. Subyek penelitian diambil secara acak sederhana (n=40) mahasiswa JPOK-FKIP UNS semester III, dibagi menjadi 4 kelompok: (1) minum antioksidan vitamin lalu lari 2x800 m (2) lari 2x800 m lalu 20 jam kemudian minum antioksidan vitamin (3) minum antioksidan vitamin lalu lari 1500 m (4) lari 1500 m lalu 20 jam kemudian minum antioksidan vitamin. Kerusakan otot diukur berdasarkankadar MDA plasma dengan metode TBARS 48 jam setelah perlakuan. Antioksidan vitamin terdiri vitamin C 200 mg, vitamin E 50 mg, vitamin A 30 mg, Zn 15 mg, Se 25 mcg. Analisis data menggunakan t-test dengan tingkat kepercayaan 95%, dengan komputer minitab for Window release 13.Hasil: Terjadi perbedaan pengaruh yang bermakna terhadap kerusakan otot antara pemberian antioksidan vitamin sebelum dengan sesudah aktivitas fisik (thit 3,70>ttab 1,68). Pemberian antioksidan vitamin sesudah aktivitas fisik kerusakan otot lebih kecil dibanding sebelum aktivitas fisik. (MDA 200,60><222,38).Simpulan: Pemberian antioksidan vitamin sesudah aktivitas fisik kerusakan otot lebih kecil dibanding sebelum aktivitas fisik.